Conflict Management Policy on Oil Palm Plantations in Riau Province: Islamic Review - Hayatul Ismi; Yeni Kusumawaty (Islamic Research, 2022)
Riau Province has a large area of oil palm plantations. Of the land area of 2.32 million hectares, 1.53 million hectares are oil palm plantations owned by the community. In 2019, there were 51 cases of natural resource conflicts in Riau Province, of which the plantation sector was the most with 40 cases (78.40 percent). This study applied a qualitative descriptive method to understand the phenomenon of plantation land conflict that aimed to: (1) identify the factors that cause conflicts in oil palm plantations in Riau Province; (2) identify current policies related to the handling of plantation conflicts and (3) recommend policy suggestions that better protect the interests of the community from an Islamic perspective. This study concluded as follow: (1) the causes of land conflicts identified are non-legal factor which is related to the management of land use and access, and legal factor which is related to judicial and regulation overlap; (2) Regarding the current policies related to plantation land conflicts, the development of oil palm plantations is basically in line with the mandate of the 1945 Constitution that natural resources are controlled by the state and used for the prosperity of the people.; (3) to protect the community interests in plantation land, this study recommends policy based on Islamic guidelines in land ownership. Islamic law classifies ownership into individual property rights (al-milkiyah al-khassah), collective property rights (al-milkiyyah al-'ammah) and state property rights (al-milkiyah al-daulah). This classification protects the community's property rights individually and collectively because investors cannot dictate the state to take over community ownership. Islam also has rules for activating inactive land and distributing it to people who can manage it, which will be the solution to unauthorized land use that is prone to conflict.